2012
DOI: 10.1097/opx.0b013e31823ee062
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Prevalence of Age-Related Cataract: Waterloo Eye Study

Abstract: Logistic regression modeling indicates that being female in this optometric clinic population was associated with an increased prevalence of CC, mixed cataract, surgical intervention, and later age of first LE. These data are important for public health planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A Waterloo Eye Study by reviewing of 6397 clinic files found that diagnosis of T2D resulted in an earlier development of all three cataract subtypes [ 8 ]. Similarly in the present study, we found that the risks of CC and PSC were elevated for patients with the T2D ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Waterloo Eye Study by reviewing of 6397 clinic files found that diagnosis of T2D resulted in an earlier development of all three cataract subtypes [ 8 ]. Similarly in the present study, we found that the risks of CC and PSC were elevated for patients with the T2D ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The cataract incidence was estimated 3.31 per 1000 person-years of type 2 diabetic patients during 3.6 years’ follow-up [ 4 ]. However, studies [ 5 - 8 ] found that not all types of cataracts [ 9 ], nuclear sclerosis (NS), cortical cataract (CC) or posterior subcapsular (PSC), are more prone to occurring in type 2 diabetes (T2D) patients. Evidence for their association has not been systematically assessed.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Previous studies focused on prevalence differences of three specific types of lens opacity: nuclear sclerosis, C cataract, and P cataract. Owing to variation of subject race and age, nuclear sclerosis is most commonly noted in Canadian, Chinese, and American whites, [15][16][17] while African, Japanese, and Singaporean present higher prevalence of C cataract than nuclear sclerosis. 16 However, there is scant information about certain factors among different types of lens opacity.…”
Section: Discussionmentioning
confidence: 99%
“…It is rare for patients to seek treatment for cataract with a single cataract type, so it may not be possible to differentiate these effects in a patient population. 26,27 Additionally, the Lens Opacities Classification System III has remained a mainstay in both clinical practice and research since the early 1990s; however, this test does not take into account specific lens features of cataract, such as water clefts, vacuoles, focal dots, and retro dots, which may affect color vision measurements in different ways. 28,29 The change in visual acuity will not be a factor in explaining the results because the low-vision CCT is designed specifically for use in low vision and performance is independent of visual acuity.…”
Section: Discussionmentioning
confidence: 99%